Biomass degradable particles and preparation method thereof

By modifying reed powder and selecting filler, combining reed powder and granulating technology, the problems of poor compatibility and high cost in wood-plastic composite materials are solved, and high performance, degradable biomass can be achieved The preparation of degraded particles is suitable for a variety of application fields.

CN119144085AInactive Publication Date: 2024-12-17JIANGXI CREDIBLE FIRE EQUIP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411634074.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, reed powder has problems such as poor compatibility between biomass and polymer matrix, thermal oxidation and degradation, and high production costs when preparing wood-plastic composite materials, resulting in unstable material performance and insufficient processing performance, making it difficult to achieve large-scale application.

Method used

By modifying the reed powder, including sulfonylation and aminolation, it increases its compatibility with polypropylene, and selects specific fillers and compatible agents to combine, it adopts intensive refining and granulation processes to prepare good ones with good ones. Biomass degradable particles with mechanical properties and degradation properties.

Benefits of technology

Significantly improves the compatibility of reed powder and polypropylene matrix, improves the overall performance and stability of the material, improves the proportion of biomass components, improves the processing performance and appearance quality, and achieves excellent mechanical properties and thermal stability. and biodegradability, suitable for packaging, agriculture and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144085A_ABST
    Figure CN119144085A_ABST
Patent Text Reader

Abstract

The invention provides a biomass degradable particle and a preparation method thereof, and belongs to the technical field of biomass materials. The biomass degradable particles are prepared from the following raw materials in parts by weight: 15 to 30 parts of modified reed powder, 50 to 70 parts of polypropylene, 5 to 20 parts of filler and 1 to 5 parts of compatilizer, the reed powder is used as a main filling material, the compatibility of the reed powder and polypropylene is improved by modifying the reed powder, and dispersion and fusion among the components are further enhanced by matching with the use of the compatilizer; by selecting the specific filler, the processability and appearance quality of the material are optimized, so that the prepared particles have excellent mechanical properties, thermal stability and degradability. The preparation method disclosed by the invention is simple and easy to realize industrialization, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomass materials, and in particular relates to a biomass degradable particle and a preparation method thereof. Background Art

[0002] With the improvement of environmental protection awareness, the development and application of biomass degradable materials have received more and more attention. Traditional plastic products are difficult to degrade and are not environmentally friendly, which limits their application. Reed is a renewable resource. Its fiber structure and biodegradability make it an ideal raw material for preparing biomass materials. Reed powder is a fine particle or powder obtained by crushing and drying reeds. Reed powder is a natural biomass material that can be degraded and is environmentally friendly. It is widely used in the manufacture of environmentally friendly materials and products.

[0003] At present, there have been a lot of studies on the application of reed powder as a raw material in wood-plastic composite materials. The patent with publication number CN104804448A discloses a factory-based production method of reed wood-plastic composite materials. The preparation method includes using steam explosion or spiral extrusion micro-carbonization to make reed raw materials into fiberized reed powder, placing the fiberized reed powder, plastic matrix and additives in a mixer and mixing them evenly, granulating the materials in a granulator before extruding them, or directly extruding the materials, and the resulting reed wood-plastic composite materials have excellent physical properties. However, the method of treating the reed fiberization in this method consumes a lot of energy and has high requirements for equipment. In addition, the patent with publication number CN118325225A discloses a preparation method and product of an environmentally friendly wood-plastic composite material for outdoor fences. The main steps are: take kaolin intercalation compound and modified reed powder, add them to the resin monomer mixed solution, ultrasonically disperse, add Ziegler-Natta catalyst during stirring, stir and react under heating conditions, cool and dry after the reaction to obtain masterbatch; blend the masterbatch with lubricant, compatibilizer, antioxidant and filler in a molten state to obtain an environmentally friendly wood-plastic composite material. It can be seen that there are certain limitations in mechanical properties and processing properties when directly using materials such as reed powder to prepare wood-plastic composite materials, such as: poor compatibility between biomass and polymer matrix, resulting in unstable material properties; easy thermal oxidation degradation during processing, affecting product quality; high production cost, difficult to achieve large-scale application. Therefore, it is of great practical significance to develop a biodegradable material with high biomass content, excellent performance, good processing performance and moderate cost. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a biomass degradable particle and a preparation method thereof. By modifying the reed powder, its compatibility with polypropylene is increased, and a specific filler is selected and matched with a compatibilizer to enable the interaction between the components and improve the material properties. Through the mixing and granulation process, particles with good mechanical properties and degradation properties are prepared.

[0005] To achieve the purpose of the invention, the technical solution adopted by the present invention is: a biomass degradable particle, the raw material composition of the biomass degradable particle is: 15-30 parts of modified reed powder, 50-70 parts of polypropylene, 5-20 parts of filler, and 1-5 parts of compatibilizer by weight; the preparation method of the modified reed powder comprises the following steps: S1, screening reed powder with a particle size of 10-100 μm and drying; S2, dispersing the reed powder described in step S1 in an organic solvent, slowly adding a sulfonylating agent and an organic base at 0-5°C for 2-4 hours to obtain a reaction mixture; then filtering, washing with dichloromethane and water in sequence, and vacuum drying to obtain activated reed powder; S3, stirring the activated reed powder obtained in step S2 and the amine compound at 60-90° C. for 4-8 hours, cooling to room temperature, washing with ethanol and water in sequence, and vacuum drying to obtain the modified reed powder; The organic solvent is at least one of dichloromethane, tetrahydrofuran, acetone, and ethyl acetate; the sulfonylating agent is at least one of toluenesulfonyl chloride and benzenesulfonyl chloride; the organic base is selected from at least one of triethylamine, pyridine, and N,N-diisopropylethylamine; and the amine compound is at least one of ethylenediamine and propylenediamine.

[0006] The main components of the reed powder of the present invention are cellulose, hemicellulose and lignin and a small amount of soluble sugar. Among them, cellulose accounts for the main proportion, which makes the reed powder have good mechanical properties and high strength. However, cellulose and hemicellulose are hydrophilic, which means that they have poor compatibility with polypropylene matrix materials, which greatly affects the performance of the final product. The present invention greatly improves the compatibility problem between biomass reed powder and polypropylene matrix by modifying reed powder, thereby improving the overall performance and stability of particles.

[0007] In the preparation method of the modified reed powder of the present invention, the reed powder is first sulfonylated to increase the reactivity of the reed powder, so that the subsequent amination reaction is easier to carry out. At the same time, the sulfonylation mainly occurs on the hydroxyl group of the reed powder, and other structures will not be excessively damaged. The reaction is carried out under relatively mild conditions, which reduces the damage to the main chain of the reed powder and better maintains the structural integrity of the reed powder. In addition, the selection of the particle size of the reed powder of the present invention can make it fully modified, evenly distributed in the matrix, improve the processing performance of the material, and help to evenly disperse and have good fluidity during extrusion or molding. If the reed powder is too large, it will cause larger gaps and uneven filling inside the material, affecting the processing fluidity and uniformity, while reducing the strength and durability of the material; if the reed powder particle size is too small, the dispersion difficulty increases, and the too small particle size leads to insufficient strength itself, which is easy to break or deform during processing or use, thereby affecting the performance of the final material.

[0008] The selection of fillers in the present invention is intended to increase the overall performance and stability of the degradable particles, while adjusting the density and degradation rate of the particles to a certain extent. The use of a compatibilizer further increases the compatibility between the components, and the components can be stably mixed. By using a compatibilizer, the interfacial tension between the components can be reduced, the uniformity and bonding strength of the materials can be improved, and thus the overall performance of the particles can be increased. Polypropylene, as the main plastic matrix, provides the basic mechanical strength and durability of the degradable particles.

[0009] Preferably, in step S2 of the preparation method of the modified reed powder, the mass ratio of the sulfonylating agent to the reed powder is 0.5-2:1, and the molar ratio of the sulfonylating agent to the organic base is 1:1.1-1.5; in step S3, the mass ratio of the activated reed powder to the amine compound is 1:3-8. The reaction at the above ratio ensures the effective progress of the modification reaction, avoids the occurrence of side reactions, and ensures the quality and performance of the modified reed powder.

[0010] More preferably, in step S2 of the preparation method of the modified reed powder, the mass ratio of the sulfonylating agent to the reed powder is 1-1.5:1, and the molar ratio of the sulfonylating agent to the organic base is 1:1.2-1.3; in step S3, the mass ratio of the activated reed powder to the amine compound is 1:4-6. Under the preferred ratio, it is helpful to reduce the occurrence of side reactions and improve the yield of the desired modified product.

[0011] Preferably, the organic solvent is dichloromethane, the sulfonylating agent is toluenesulfonyl chloride, the organic base is triethylamine, and the amine compound is ethylenediamine. The present invention selects the organic solvent, the sulfonylating agent and the organic base to ensure the improvement of the reaction rate, wherein triethylamine has mild alkalinity and will not cause serious degradation of reed powder; it is easy to mix with the organic solvent, has a suitable boiling point, and is easy to remove after the reaction. At the same time, by controlling the washing and drying steps, the product yield is improved, and the purity and stability of the modified reed powder are guaranteed.

[0012] Preferably, the vacuum drying conditions in step S2 of the preparation method of the modified reed powder are pressure 0.05-0.1 mbar, temperature 50-70°C, and drying time 8-16 h; the vacuum drying conditions in step S3 are pressure 0.05-0.1 mbar, temperature 50-70°C, and drying time 20-28 h.

[0013] Preferably, the polypropylene is a high melt index polypropylene, with a melt index of 10-30 g / 10 min and a weight average molecular weight of 150,000-250,000. The polypropylene of the present invention selects a suitable melt index and molecular weight, which well balances the processability and strength properties of the material. A higher molecular weight helps to improve the strength and rigidity of polypropylene while also maintaining suitable processability. Preferably, the filler is composed of calcium carbonate and titanium dioxide, the mass ratio of calcium carbonate to titanium dioxide is 1-5:1, the particle size of calcium carbonate is 0.5-50 μm, and the particle size of titanium dioxide is 100-400 nm.

[0014] The filler of the present invention is a combination of calcium carbonate and titanium dioxide, and a specific mass ratio is selected to improve the hardness and rigidity of polypropylene and improve dimensional stability; wherein the added calcium carbonate reduces the melt viscosity during the extrusion process and improves the processing performance. The addition of titanium dioxide improves the apparent quality of the particles, making the product look more uniform and beautiful, and at the same time improves the product's UV resistance and weather resistance.

[0015] Preferably, the compatibilizer is at least one of maleic anhydride grafted polypropylene, vinyl alcohol-ethylene copolymer and ethylene-propylene copolymer. The compatibilizer of the present invention increases the dispersion compatibility of the modified reed powder and polypropylene on the one hand, and on the other hand, the compatibilizer can effectively adhere to the surface of the filler, forming an interface layer on the surface of the filler that can interact with the polypropylene matrix, so that it is evenly dispersed in the polymer matrix, thereby enhancing the compatibility between the filler and the polypropylene.

[0016] Preferably, the grafting rate of the maleic anhydride grafted polypropylene is 0.5-2%. The grafting rate of the maleic anhydride grafted polypropylene has a good effect within the above range, and too high a grafting rate will lead to decreased fluidity.

[0017] In another aspect, the present invention provides a method for preparing the above-mentioned biodegradable particles, and the specific steps of the preparation method are as follows: S4. Add the modified reed powder and the compatibilizer into a high-speed mixer according to the formula amount, and mix them at a temperature of 80-120° C. and a speed of 500-1000 rpm for 5-10 minutes to obtain pre-mixed modified reed powder; S5. According to the formula amount, the premixed modified reed powder obtained in step S4 is added into an internal mixer together with polypropylene and filler, and mixed and kneaded for 10-20 minutes at a temperature of 160-180° C. and a rotation speed of 40-100 rpm; and then sent into an extruder for extrusion granulation to obtain the biomass degradable particles.

[0018] In the method for preparing biomass degradable particles of the present invention, the modified reed powder is premixed with a compatibilizer and then mixed with other components. This method can give full play to the role of the compatibilizer, so that the reed powder is more easily dispersed into the polypropylene matrix in the subsequent mixing. The compatibilizer can be evenly coated on the surface of the modified reed powder during the premixing process, enhancing its interfacial compatibility with polypropylene, thereby improving the performance of the final product. At the same time, stirring at a higher speed can effectively break up the reed powder agglomeration, ensure full contact with the compatibilizer, and avoid the uneven phenomenon that may occur in the subsequent granulation process. The appropriate mixing time can ensure full mixing and avoid material degradation caused by excessive shearing. The selection of the banburying temperature, rotation speed and time ensures that the components are evenly mixed to avoid material degradation caused by overheating.

[0019] Preferably, the granulation is carried out using a twin-screw extruder, the extrusion temperature is 180-200° C., and the screw speed is 100-150 rpm.

[0020] Preferably, the biodegradable particles have a length of 2-5 mm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention uses reed powder as the main biomass filling material, which improves the environmental friendliness and renewability of the material. By subjecting the reed powder to sulfonylation and amination treatments, the compatibility between the reed powder and the polypropylene matrix is ​​significantly improved, thereby improving the overall performance and stability of the particles. At the same time, the present invention synergizes with the compatibilizer to increase the proportion of biomass components in the material and improves the degradability of the material.

[0023] (2) By selecting fillers with specific particle sizes and proportions and adding compatibilizers, the processing performance, appearance quality and strength performance of the material are improved. The biodegradable particles of the present invention have excellent mechanical properties, thermal stability and degradability, and can be widely used in packaging, agriculture, daily necessities and other fields.

[0024] (3) The preparation method of the present invention is simple, easy to realize industrial production, and has good application prospects and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a SEM image of the modified reed powder in Example 1; Figure 2 is a SEM image of the modified reed powder in Example 2; Figure 3 is a SEM image of the modified reed powder in Example 3; Figure 4 is a SEM image of the modified reed powder in Example 4; Figure 5 is the Fourier infrared absorption spectrum of the modified reed powder prepared in Example 1-4; Figure 6 is a SEM image of the calcium carbonate raw material in Example 5; Figure 7 is a SEM image of the titanium dioxide raw material in Example 5; Figure 8 is a SEM image of the polypropylene raw material particles in Example 5; Fig. 9 is a SEM image of the surface of the biodegradable particles obtained in Example 5; Fig.10 is a SEM image of the surface of the biodegradable particles obtained in Example 6; Fig.11 is a SEM image of the surface of the biodegradable particles obtained in Example 10; Fig.12 is an optical photograph of the biodegradable particles obtained in Example 15; Fig.13 This is an optical photograph of the molded product prepared in Example 15. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention, technical process steps, and specific implementation conditions to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The chemical reagents used in the present invention are commercially available. Example 1

[0027] Reed powder with an average particle size of 50 μm was screened and dried; 10 g of the dried reed powder was dispersed in 100 mL of dichloromethane, and 15 g of a dichloromethane solution (40 mL) of toluenesulfonyl chloride and 10 mL of triethylamine were slowly added dropwise at a temperature of 0-5°C, and the mixture was stirred for reaction for 3 hours to obtain a reaction mixture, which was then poured into ice water for filtration, and the filter cake was repeatedly washed with dichloromethane and deionized water in turn, and then dried at 60°C and 0.05 mbar vacuum conditions for 12 hours to obtain activated reed powder. 8 g of activated reed powder was added to 40 mL of ethylenediamine, stirred and reacted at 75°C for 5 hours, cooled to room temperature, and repeatedly washed with ethanol and deionized water in turn, and then dried at 60°C and 0.05 mbar vacuum conditions for 24 hours to obtain modified reed powder, which was characterized by scanning electron microscopy. The microstructure was as follows: Figure 1 As shown in Figure 2, the particle size distribution of the modified reed powder is 0.5 μm~120 μm. The prepared modified reed powder was further characterized by Fourier infrared absorption spectroscopy, as shown in Figure 2. Figure 5 As shown, the results show that the modified reed powder has obvious absorption peaks at 2856, 1647 and 1574 cm-1, respectively. These three peaks are the absorption peaks of -CH2-, -C=N- and -CN- functional groups, respectively, indicating that the reed powder is successfully grafted with amino and sulfonyl groups with high chemical reactivity. The yield of the modified reed powder in this example is about 85.4%. Example 2

[0028] Reed powder with an average particle size of 10 μm was screened and dried; 10 g of the dried reed powder was dispersed in 100 mL of tetrahydrofuran, and 20 g of toluenesulfonyl chloride tetrahydrofuran solution (50 mL) and 10 mL of pyridine were slowly added dropwise at a temperature of 0-5°C, and the mixture was stirred for reaction for 4 hours to obtain a reaction mixture, which was then poured into ice water for filtration, and the filter cake was repeatedly washed with dichloromethane and deionized water in turn, and then dried at 70°C and 0.08 mbar vacuum conditions for 8 hours to obtain activated reed powder. 8 g of activated reed powder was added to 24 mL of propylenediamine, stirred and reacted at 90°C for 4 hours, cooled to room temperature, and repeatedly washed with ethanol and deionized water in turn, and then dried at 70°C and 0.08 mbar vacuum conditions for 20 hours to obtain modified reed powder, which was characterized by scanning electron microscopy. The microstructure was as follows: Figure 2 As shown in Figure 2, the particle size distribution of the modified reed powder is 0.8 μm~150 μm. The prepared modified reed powder was further characterized by Fourier transform infrared absorption spectroscopy, as shown in Figure 2. Figure 5 As shown, the results show that the modified reed powder has obvious absorption peaks at 2856, 1647 and 1574 cm-1, respectively. These three peaks are the absorption peaks of -CH2-, -C=N- and -CN- functional groups, respectively, indicating that the reed powder is successfully grafted with amino and sulfonyl groups with high chemical reactivity. The yield of the modified reed powder in this example is about 80.8%. Example 3

[0029] Reed powder with an average particle size of 100 μm was screened and dried; 10 g of the dried reed powder was dispersed in 100 mL of acetone, and 5 g of an acetone solution of benzenesulfonyl chloride (20 mL) and 5 mL of N, N-diisopropylethylamine were slowly added at a temperature of 0-5°C, and the mixture was stirred for reaction for 2 hours to obtain a reaction mixture, which was then poured into ice water for filtration, and the filter cake was repeatedly washed with dichloromethane and deionized water, and then dried at 50°C and 0.1 mbar vacuum conditions for 16 hours to obtain activated reed powder. 8 g of activated reed powder was added to 64 mL of ethylenediamine, stirred and reacted at 60°C for 8 hours, cooled to room temperature, and repeatedly washed with ethanol and deionized water, and then dried at 50°C and 0.1 mbar vacuum conditions for 28 hours to obtain modified reed powder, which was characterized by scanning electron microscopy. The microstructure was as follows: Figure 3 As shown in Figure 2, the particle size distribution of the modified reed powder is 15 μm~500 μm. The prepared modified reed powder was further characterized by Fourier infrared absorption spectroscopy, as shown in Figure 2. Figure 5 As shown, the results show that the modified reed powder has obvious absorption peaks at 2856, 1647 and 1574 cm-1, respectively. These three peaks are the absorption peaks of -CH2-, -C=N- and -CN- functional groups, respectively, indicating that the reed powder is successfully grafted with amino and sulfonyl groups with high chemical reactivity. The yield of the modified reed powder in this example is about 75.6%. Example 4

[0030] Reed powder with an average particle size of 60 μm was screened and dried; 10 g of the dried reed powder was dispersed in 100 mL of ethyl acetate, and 10 g of toluenesulfonyl chloride ethyl acetate solution (30 mL) and 6 mL of triethylamine were slowly added dropwise at a temperature of 0-5°C, and the mixture was stirred for reaction for 3 hours to obtain a reaction mixture, which was then poured into ice water for filtration, and the filter cake was repeatedly washed with dichloromethane and deionized water in turn, and then dried at 60°C and 0.05 mbar vacuum conditions for 12 hours to obtain activated reed powder. 8 g of activated reed powder was added to 50 mL of ethylenediamine, stirred and reacted at 75°C for 5 hours, cooled to room temperature, and repeatedly washed with ethanol and deionized water in turn, and then dried at 60°C and 0.05 mbar vacuum conditions for 24 hours to obtain modified reed powder for scanning electron microscopy characterization. The microstructure is as follows: Figure 4 As shown in Figure 2, the particle size distribution of the modified reed powder is 20 μm~720 μm. The prepared modified reed powder was further characterized by Fourier transform infrared absorption spectroscopy, as shown in Figure 2. Figure 5As shown, the results show that the modified reed powder has obvious absorption peaks at 2856, 1647 and 1574 cm-1, respectively. These three peaks are the absorption peaks of -CH2-, -C=N- and -CN- functional groups, respectively, indicating that the reed powder is successfully grafted with amino and sulfonyl groups with high chemical reactivity. The yield of the modified reed powder in this example is about 82.4%. Example 5

[0031] The raw materials of the biodegradable particles described in this embodiment are arranged in parts by weight: 30 parts of the modified reed powder prepared in Example 1, 50 parts of polypropylene, 20 parts of filler (15 parts of calcium carbonate, 5 parts of titanium dioxide), and 3 parts of maleic anhydride grafted polypropylene; the modified reed powder and maleic anhydride grafted polypropylene are added into a high-speed mixer according to the formula amount, and mixed at a temperature of 100° C. and a speed of 800 rpm for 8 minutes to obtain a premixed modified reed powder; the premixed modified reed powder obtained is mixed with polypropylene (melt index 25 g / 10min, weight average molecular weight 200,000), calcium carbonate (particle size 20μm), titanium dioxide (particle size 200nm) are added to an internal mixer and mixed at 180°C and 80rpm for 10min; then they are sent to a twin-screw extruder and extruded and granulated at 200°C and 150rpm to obtain the biomass degradable particles; the raw materials calcium carbonate, titanium dioxide, polypropylene and the obtained biomass degradable particles are characterized by scanning electron microscopy, and the microstructure is as follows Figure 6-9 As shown, it can be seen that the sizes of calcium carbonate, titanium dioxide, and polypropylene are 0.4 μm~36 μm, 20 nm~50 nm, and 80 μm~120 μm, respectively, and there are a small amount of particles and cracks on the surface of the obtained biomass degradable particles, indicating that the raw materials used in this example have good compatibility. Example 6

[0032] The raw materials of the biodegradable particles described in this embodiment are arranged in weight: 15 parts of modified reed powder prepared in Example 2, 70 parts of polypropylene, 15 parts of fillers (12 parts of calcium carbonate, 3 parts of titanium dioxide), and 1 part of maleic anhydride grafted polypropylene; the modified reed powder and maleic anhydride grafted polypropylene are added to a high-speed mixer according to the formula amount, and mixed at a temperature of 80°C and a speed of 1000rpm for 5 minutes to obtain pre-mixed modified reed powder; the obtained pre-mixed modified reed powder is added to an internal mixer together with polypropylene (melt index 20 g / 10min, weight average molecular weight 250,000), calcium carbonate (particle size of 10μm), and titanium dioxide (particle size of 150nm) according to the formula amount, and mixed at 175°C and a speed of 100rpm for 6 minutes; then the particles are sent to a twin-screw extruder for extrusion granulation at 195°C and 140rpm to obtain the biodegradable particles, which are characterized by scanning electron microscopy. The microstructure is as follows: Fig.10As shown, there are almost no particles and cracks on the surface of the obtained biomass degradable particles, indicating that the raw materials used in this example have very good compatibility. Example 7

[0033] The raw materials of the biomass degradable particles described in this embodiment are arranged in groups by weight: 20 parts of the modified reed powder prepared in Example 3, 60 parts of polypropylene, 20 parts of filler (12 parts of calcium carbonate, 8 parts of titanium dioxide), and 5 parts of maleic anhydride grafted polypropylene; the modified reed powder and maleic anhydride grafted polypropylene are added to a high-speed mixer according to the formula amount, and mixed at a temperature of 120° C. and a speed of 500 rpm for 10 minutes to obtain a premixed modified reed powder; the obtained premixed modified reed powder is added to a banbury mixer together with polypropylene (melt index 10 g / 10min, weight average molecular weight 250,000), calcium carbonate (particle size of 0.5 μm), and titanium dioxide (particle size of 100 nm) according to the formula amount, and banburyed for 10 minutes at 180° C. and a speed of 50 rpm; and then sent to a twin-screw extruder for extrusion granulation at 200° C. and 150 rpm to obtain the biomass degradable particles. Example 8

[0034] The raw materials of the biomass degradable particles described in this embodiment are composed by weight: 20 parts of the modified reed powder prepared in Example 4, 60 parts of polypropylene, 17 parts of filler (14 parts of calcium carbonate, 3 parts of titanium dioxide), and 3 parts of compatibilizer (1.5 parts of vinyl alcohol-ethylene copolymer and 1.5 parts of ethylene-propylene copolymer); the modified reed powder, vinyl alcohol-ethylene copolymer and ethylene-propylene copolymer are added into a high-speed mixer according to the formula amount, and mixed at a temperature of 100° C. and a speed of 800 rpm for 8 minutes to obtain a premixed modified reed powder; the premixed modified reed powder obtained is mixed with polypropylene (melt index 30 g / 10min, weight average molecular weight 150,000), calcium carbonate (particle size 50μm), and titanium dioxide (particle size 400nm) are added into an internal mixer and mixed for 10min at 160°C and 80rpm; then they are sent into a twin-screw extruder and extruded and granulated at 180°C and 100rpm to obtain the biomass degradable particles. Example 9

[0035] The raw materials of the biodegradable particles described in this embodiment are composed by weight: 30 parts of the modified reed powder prepared in Example 1, 60 parts of polypropylene, 5 parts of filler (2.5 parts of calcium carbonate, 2.5 parts of titanium dioxide), and 3 parts of compatibilizer (1.5 parts of vinyl alcohol-ethylene copolymer and 1.5 parts of ethylene-propylene copolymer); the modified reed powder, vinyl alcohol-ethylene copolymer and ethylene-propylene copolymer are added into a high-speed mixer according to the formula amount, and mixed at a temperature of 100° C. and a speed of 800 rpm for 8 minutes to obtain a premixed modified reed powder; the premixed modified reed powder obtained is mixed with polypropylene (melt index 30 g / 10min, weight average molecular weight 150,000), calcium carbonate (particle size 50μm), and titanium dioxide (particle size 400nm) are added into an internal mixer and kneaded for 5 minutes at 180°C and 80rpm; then they are sent into a twin-screw extruder and extruded and granulated at 200°C and 150rpm to obtain the biomass degradable particles. Example 10

[0036] The raw materials of the biodegradable particles described in this embodiment are composed by weight: 30 parts of unmodified reed powder, 50 parts of polypropylene, 20 parts of filler (15 parts of calcium carbonate, 5 parts of titanium dioxide), and 3 parts of maleic anhydride grafted polypropylene; the preparation method of the biodegradable particles is the same as that of Example 5, and the obtained biodegradable particles are characterized by scanning electron microscopy. The microstructure is as follows: Fig.11 As shown, the obtained biomass degradable particles have obvious particles and cracks on the surface, indicating that the compatibility of the raw materials used in this example is poor. Embodiment 11

[0037] The raw materials of the biomass degradable particles described in this embodiment are arranged in groups by weight: 30 parts of modified reed powder prepared in Example 1, 50 parts of polypropylene, 20 parts of filler (15 parts of calcium carbonate, 5 parts of titanium dioxide), and no compatibilizer is added; the preparation method of the biomass degradable particles is the same as that of Example 5. Example 12

[0038] The raw materials of the biomass degradable particles described in this embodiment are arranged in groups by weight: 30 parts of modified reed powder prepared in Example 1, 50 parts of polypropylene, 20 parts of calcium carbonate, and 3 parts of maleic anhydride grafted polypropylene; the preparation method of the biomass degradable particles is the same as that of Example 5. Example 13

[0039] The raw materials of the biomass degradable particles described in this embodiment are arranged in groups by weight: 30 parts of modified reed powder prepared in Example 1, 50 parts of polypropylene, 20 parts of titanium dioxide, and 3 parts of maleic anhydride grafted polypropylene; the preparation method of the biomass degradable particles is the same as that of Example 5. Embodiment 14

[0040] The raw materials of the biomass degradable particles described in this embodiment are arranged in groups by weight: 40 parts of modified reed powder prepared in Example 1, 40 parts of polypropylene, 20 parts of filler (15 parts of calcium carbonate, 5 parts of titanium dioxide), and 3 parts of maleic anhydride grafted polypropylene; the preparation method of the biomass degradable particles is the same as that of Example 5.

[0041] The biodegradable particles prepared in Examples 5-9 and 10-14 were tested for melt index according to GB / T 3682.1-2018, heat deformation temperature according to GB / T 1634-2004, and bending properties according to GB / T 9341-2008. Table 1 shows the raw material weight distribution ratio of the biodegradable particles in Examples 5-9 and 10-14. Table 2 shows the performance parameters of the biodegradable particles in Examples 5-9 and 10-14.

[0042] Table 1

[0043] It can be seen from Examples 1-4 that in the preparation process of modified reed powder, the ratio of reactants and the change of reaction conditions will affect the yield of modified reed powder products to a certain extent. As can be seen from Table 2, the biomass degradable particles obtained in Examples 5-9 all have a uniform and glossy appearance, which indicates that the material has good dispersibility and formability. The density of the particles prepared in Examples 5-9 is 0.95-1.08g / cm³, and has a high heat deformation temperature, indicating good heat resistance; the melt index is moderate, which means that it has good processing performance; the flexural modulus ranges from 1.8-2.3GPa, indicating that it has good rigidity.

[0044] The only difference between Example 10 and Example 5 is that the reed powder is not modified; the appearance of the obtained particles is uneven, and the heat deformation temperature and bending modulus are significantly reduced, indicating that the modification treatment improves the appearance uniformity of the particles and improves the heat deformation temperature and strength performance. Figure 7 and Fig. 9By comparison, it can be seen that the modified reed powder can be mixed well with other materials without interface incompatibility. The unmodified reed powder has interface incompatibility, which affects the overall performance of the particles. The difference between Example 11 and Example 6 is that no compatibilizer is added; the heat deformation temperature and bending modulus of the obtained particles decrease, and the melt index decreases, indicating that the addition of a compatibilizer improves the uniformity of the particles, and improves the heat deformation temperature and processing performance. The difference between Examples 12 and 13 and Example 5 is that only a single calcium carbonate or titanium dioxide is used as a filler, resulting in a significant decrease in modulus, indicating that the combined filler of calcium carbonate and titanium dioxide has better strength performance and processability than a single calcium carbonate filler. In Example 14, the proportion of reed powder is increased, which has a higher biodegradability rate, but the modulus performance decreases significantly.

[0045] Table 2 Embodiment 15

[0046] Granulation was performed using the process and raw materials of Example 5 to obtain biodegradable particles such as Fig.12 The pellets are then added to an extrusion thermoforming mold for shaping. The extrusion thermoforming temperature is 205°C to obtain a molded product as shown. Fig.13 shown.

[0047] Technical personnel should note that although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.

Claims

1. A biodegradable particle, characterized in that: The raw material composition of the biomass degradable particles is: 15-30 parts of modified reed powder, 50-70 parts of polypropylene, 5-20 parts of filler and 1-5 parts of compatibilizer by weight. The preparation method of the modified reed powder comprises the following steps: S1, screening reed powder with a particle size of 10-100 μm and drying; S2, dispersing the reed powder described in step S1 in an organic solvent, slowly adding a sulfonylating agent and an organic base at 0-5°C for 2-4 hours to obtain a reaction mixture; then filtering, washing with dichloromethane and water in sequence, and vacuum drying to obtain activated reed powder; S3, stirring the activated reed powder obtained in step S2 and the amine compound at 60-90° C. for 4-8 hours, cooling to room temperature, washing with ethanol and water in sequence, and vacuum drying to obtain the modified reed powder; The organic solvent is at least one of dichloromethane, tetrahydrofuran, acetone, and ethyl acetate; the sulfonylating agent is at least one of toluenesulfonyl chloride and benzenesulfonyl chloride; the organic base is selected from at least one of triethylamine, pyridine, and N,N-diisopropylethylamine; and the amine compound is at least one of ethylenediamine and propylenediamine.

2. The biodegradable particle according to claim 1, characterized in that: In step S2 of the preparation method of the modified reed powder, the mass ratio of the sulfonylating agent to the reed powder is 0.5-2:1, and the molar ratio of the sulfonylating agent to the organic base is 1:1.1-1.5; in step S3, the mass ratio of the activated reed powder to the amine compound is 1:3-8.

3. A biodegradable particle according to claim 1 or 2, characterized in that: The vacuum drying conditions in step S2 of the preparation method of the modified reed powder are a pressure of 0.05-0.1 mbar and a temperature of 50-70°C; the vacuum drying conditions in step S3 are a pressure of 0.05-0.1 mbar and a temperature of 50-70°C.

4. The biodegradable particle according to claim 1, characterized in that: The melt index of the polypropylene is 10-30 g / 10min, and the weight average molecular weight of the polypropylene is 150,000-250,000.

5. The biodegradable particle according to claim 1, characterized in that: The filler is composed of calcium carbonate and titanium dioxide, the mass ratio of calcium carbonate to titanium dioxide is 1-5:1, the particle size of calcium carbonate is 0.5-50 μm, and the particle size of titanium dioxide is 100-400 nm.

6. The biodegradable particle according to claim 1, characterized in that: The compatibilizer is at least one of maleic anhydride grafted polypropylene, vinyl alcohol-ethylene copolymer and ethylene-propylene copolymer.

7. A method for preparing biodegradable particles according to any one of claims 1 to 6, characterized in that: The specific steps of the preparation method are as follows: S4. Add the modified reed powder and the compatibilizer into a high-speed mixer according to the formula amount, and mix them at a temperature of 80-120° C. and a speed of 500-1000 rpm for 5-10 minutes to obtain pre-mixed modified reed powder; S5. According to the formula amount, the premixed modified reed powder obtained in step S4 is added into an internal mixer together with polypropylene and filler, and mixed and kneaded for 10-20 minutes at a temperature of 160-180° C. and a rotation speed of 50-100 rpm; and then sent into an extruder for extrusion granulation to obtain the biomass degradable particles.

8. The method for preparing biodegradable particles according to claim 7, characterized in that: In step S5, a twin-screw extruder is used for granulation, the extrusion temperature is 180-200° C., and the screw speed is 100-150 rpm.

Citation Information

Patent Citations

  • Industrialized production method of reed and wood-plastic composite material

    CN104804448A

  • Preparation method of environment-friendly wood-plastic composite material for outdoor fence and product thereof

    CN118325225A

  • Novel environment-friendly wood-plastic wall board and preparation method thereof

    CN108864570A

  • Degradable bio-based polyethylene preparation system

    CN113150427A

  • Composite board using straws and reeds to reinforce red mud minerals and preparation method of composite board

    CN117050411A